Characteristics and prognosis of primary malignant melanoma of the esophagus. Issue 28 (10th July 2020) - Chen, Hengchi; Fu, Qiang; Sun, Kelin
Abstract : Abstract: Primary malignant melanoma of esophagus (PMME) is a rare malignant tumor of esophagus. This study aimed to investigate the clinic pathologic characteristics and analyze the factors that might affect the prognosis of PMME patients. A total of 20 PMME patients who underwent surgical treatment in our hospital from 1975 to 2017 were analyzed. The clinical data, surgical and pathologic features of all patients were collected. For 20 PMME patients, the average age was 57.3 ± 10.7 years, and the male patients account for 75%. Most of the tumors (95%) were located in the middle and lower of the esophagus. There were 7 patients with primary tumor invasion beyond the muscular layer (T3 + T4) and 10 patients with lymph node metastasis (LNM). The median survival time of 20 patients was 12 months, and the 1-year and 5-year survival rates were 50% and 16.9%, respectively. The probability of LNM in tumors confined to submucosa (T1) and myometrium (T2) was lower than that in tumors with deeper invasion (T3, T4) ( P  = .035). Multivariate analysis showed that tumor node metastasis (TNM) staging was the independent prognostic factor for survival of PMME patients (hazard ratio [95% confidence interval], 4.15 [1.36–12.67]; P  = .012). For PMME patients, tumors with deeper invasion were more likely to have LNM, and TNM staging was an independent predictor of prognosis for survival. Early detection of the disease and radical resection of the tumor are critical for better survival of the PMME patients.